Modulation of Gq/PLC-Mediated Signaling by Acute Lithium Exposure - Sánchez Triviño, Cesar Adolfo; Landinez, Maria Paula; Duran, Sara; Gomez, María del Pilar; Nasi, Enrico (Frontiers in Cellular Neuroscience, 2022)
Although lithium has long been one of the most widely used pharmacological agents in psychiatry, its mechanisms of action at the cellular and molecular level remain poorly understood. One of the targets of Li+ is the phosphoinositide pathway, but whereas the impact of Li+ on inositol lipid metabolism is well documented, information on physiological effects at the cellular level is lacking. We examined in two mammalian cell lines the effect of acute Li+ exposure on mobilization of internal Ca2+ and PLC-dependent membrane conductances. We first corroborated by Western blots and immuno-fluorescence in HEK293 cells the presence of key signaling elements of a muscarinic PLC pathway (M1AchR, Gq, PLC-beta1 and IP3Rs). Stimulation with carbachol evoked a dose-dependent mobilization of Ca, as determined with fluorescent indicators; this was due to release from internal stores and proved susceptible to the PLC antagonist U73122. Li+ exposure reproducibly potentiated the Ca response in a concentration-dependent manner extending to the low millimolar range. To broaden those observations to a neuronal context and probe potential Li modulation of electrical signaling, we next examined the cell line SHsy5y. We replicated the potentiating effects of Li on mobilization of internal Ca, and, after characterizing the basic properties of the electrical response to cholinergic stimulation, we also demonstrated an equally robust up-regulation of muscarinic membrane currents. Finally, by directly stimulating the signaling pathway at different links downstream of the receptor, the site of action of the observed Li effects could be narrowed down to the G protein and its interaction with PLC-beta. These observations document a modulation of Gq/PLC/IP3-mediated signaling by acute exposure to lithium, reflected in distinct physiological changes in cellular responses.